AESCHYLUS’ SUPPLIANTS . SPACIAL-CHORAL ENSAMBLE IN FOUR MOVEMENTS (Argos, 2018)
Our aim is to expose a Supplices’ compositional scheme that manages to apprehend its characteristic structural technique, facing the fixed Aristotelian pattern. The approach analyses the work of TAPLIN (1977) relating to Aeschylean tragic performance, that radically changed the performative studies by demonstrating the dramatic use of character’s exits and entrances. Given the uniqueness of Aeschylus’ Supplices regarding the leading role of the chorus and the predominance of lyrics, we hold that the analysis of its structure imposes us to revise TAPLIN ’s proposal and to consider that the choral odes are a substantial part of the acts (W ILES , 1997).
Keywords: Structure; Poetics; Taplin; Supplices; Aeschylus